2016
DOI: 10.1097/md.0000000000003320
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Daily 3-Gy Hypofractionated and 1.8-Gy Conventional Breast Irradiation in Early-Stage Breast Cancer

Abstract: We retrospectively compared accelerated hypofractionation (AHF) with conventional fractionation (CF) in the radiation therapy (RT) for early-stage breast cancer patients.Three hundred seventy-nine early-stage (pT1–2 and pN0–1a) breast cancer patients who received RT with AHF after breast-conserving surgery (BCS) were included. These patients were matched with 379 corresponding patients who received BCS and RT with CF at a different center with respect to the year BCS was performed, patient age (±3 years), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Also, the fourth trial investigated only acute and short-term toxicities (14). Three other studies were identified that compared HF+boost and CF+boost (13,15,16). However, in one of these studies, median follow-up was limited to 16 months, and one study evaluated only acute toxicity (13,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the fourth trial investigated only acute and short-term toxicities (14). Three other studies were identified that compared HF+boost and CF+boost (13,15,16). However, in one of these studies, median follow-up was limited to 16 months, and one study evaluated only acute toxicity (13,15).…”
Section: Discussionmentioning
confidence: 99%
“…However, in one of these studies, median follow-up was limited to 16 months, and one study evaluated only acute toxicity (13,15). The third of these studies provided longerterm (5-year) results of LC, MF, and OS (16). However, its results regarding acute skin toxicity were conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…After full-text scrutinization, 35 of them were further omitted for the following reasons: (1) no provision of the 5-year outcomes in 15 potential articles for calculating the weighted average proportion; (2) no application of a 10-16 Gy boost to the patient in 13 potential studies for calculating the weighted average proportion in the WBI cohort; (4) no usage of a single dose of 21 Gy in five potential studies for calculating the weighted average proportion in the IORT cohort; and (5) 2 articles with other reasons. Ultimately, 38 articles with 30,225 early breast cancer patients were involved (9-12, 15-20, 26-53), in which 18 exclusively analyzed the 5-year oncological efficacy in the WBI cohort (15,16,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41), 9 exclusively analyzed that in the IORT cohort (9,12,17,(42)(43)(44)(45)(46)(47), and 11 compared the oncological efficacy between the cohorts (10,11,(18)(19)(20)(48)(49)(50)(51)(52)(53). Three of the 11 studies for the comparative meta-analysis had the available data to calculate the weighted average 5-year oncological efficacy in the non-comparative meta-analysis (10,…”
Section: Literature Searchmentioning
confidence: 99%
“…More importantly, cosmetic outcomes are similar when a boost is used in combination with hypofractionated vs. conventional WBI (33)(34)(35)(36)(37)(38)(39). In their 120-patient study comparing addition of a boost to conventional fractionation (50 Gy/25 fractions) vs. hypofractionation (42.5 Gy/16 fractions), De Felice et al (34) found no difference in long-term breast fibrosis.…”
Section: Fractionation Schedulementioning
confidence: 99%
“…Next, with regards to cancer control, conventional and hypofractionation regiments have been shown to produce similar outcomes ( 33 ). Within conventional fractionation, the improved local control provided by a boost is well-documented ( 40 ).…”
Section: Fractionation Schedulementioning
confidence: 99%